Enterotoxins production, biofilm formation and antimicrobial resistance of Staphylococcus aureus strains isolated from refrigerated raw cow milk - Lampugnani, Camila; Montanhini, Maike Taís Maziero; Camposâ€Galvão, Maria Emilene Martino; Nero, Luis Augusto; Bersot, Luciano dos Santos (Acta Scientiarum. Technology, 2019)
This study aimed to isolate Staphylococcus aureus in refrigerated raw cow milk, and identify the presence of enterotoxin-expression genes, enterotoxin production and adherence ability, and antimicrobial resistance potential of the isolated strains. Fifty raw milk samples obtained in different dairy farms were analyzed for S. aureus and evaluated in the isolates the presence of genes associated with the production of major staphylococcal enterotoxins and biofilm formation. In vitro assays were also performed to evaluate the production of enterotoxins and adherence ability, and the antimicrobial resistance. One half (25/50) of raw milk samples presented coagulase-positive staphylococci and 95.2% of the isolates were confirmed to be S. aureus. Among them, 42.4% were carrying genes for enterotoxins production; however, only one isolate was able to produce enterotoxins. All S. aureus isolates were carrying at least two genes associated with biofilm formation and 95.2% isolates was able to adhere upon the in vitro assay. All isolates demonstrated antimicrobial resistance potential to one or more of the tested antibiotics.